Estructuracion de un índice bursátil basado en criptomonedas (2023)
This study aims to propose an index based on cryptocurrencies, considering historical data from the cryptocurrency market. The study found a diversified index that adequately replicates the behavior of the cryptocurrency market. This index provides a financial tool for investors seeking to diversify their portfolio in cryptocurrencies. It is a new investment research alternative for cryptocurrency investors as it provides a global market perspective so that investors can make strategic and informed decisions, considering the most relevant factors for financial decision-making, such as profitability, risk, market liquidity, and correlation between assets.